Effect of Zn addition on hot tearing behaviour of Mg–0.5Ca–xZn alloys. (15th December 2015) - Song, Jiangfeng; Wang, Zhi; Huang, Yuanding; Srinivasan, Amirthalingam; Beckmann, Felix; Kainer, Karl Ulrich; Hort, Norbert
Abstract: The influence of Zn addition (0, 0.5, 1.5, 4.0 and 6.0 wt.%) on hot tearing behaviour of Mg–0.5 wt.% Ca alloy was investigated using a constrained rod casting (CRC) apparatus. The effects of mould temperature and grain refinement on the hot tearing susceptibility (HTS) were studied. Hot tears were observed with 3D X-ray tomography and the tear volumes were quantified. Results show that the Zn addition increases the HTS of Mg–0.5Ca alloys. At a mould temperature of 250 °C, all alloys investigated except Mg–0.5Ca–6Zn alloy show severe HTS. An increase in the mould temperature from 250 °C to 450 °C did not reduce the HTS in Mg–0.5Ca–1.5Zn and Mg–0.5Ca–4Zn alloys. Among all the investigated alloys, Mg–0.5Ca–4Zn alloy exhibits severe HTS as it completely broke away from the sprue–rod junction. The HTS of alloys was well correlated with the susceptible temperature range (ΔTs ). An increase in ΔTs increased the HTS. The hot tears propagated along the grain boundaries through liquid film rupture. Grain refinement by Zr addition improved the hot tearing resistance of Mg–0.5Ca–4Zn alloy as the fine grain structure facilitated the easy feeding of liquid into the last area of solidification and accommodated the developed strain more effectively. Graphical abstract: Highlights: The hot tearing initiation/onset temperature was detected. The tear volume was quantified with 3D X-ray tomography technique. The effect of grain refinement on the hot tearing behaviour of Mg alloys was investigated. The impact of initial mould temperature on the hot tearing susceptibility was studied. The fracture surfaces were observed and used to clarify the hot tearing mechanism.